A Duplex-Droplet Digital PCR Assay for Simultaneous Quantitative Detection of Monilinia fructicola and Monilinia laxa on Stone Fruits - Raguseo, Celeste; Gerin, Donato; Pollastro, Stefania; Rotolo, Caterina; Rotondo, Palma Rosa; Faretra, Francesco; De Miccolis Angelini, Rita Milvia (Frontiers in Microbiology, 2021)
Brown rot, caused by different Monilinia species, is a most economically important disease of pome and stone fruits worldwide. In Europe and in Italy, the quarantine pathogen M. fructicola was recently introduced and rapidly spread and, by competing with the main indigenous species M. fructigena and M. laxa, caused relevant changes in Monilinia populations. As a result, in most areas, the pathogen almost replaced M. fructigena and now coexists with M. laxa. The availability of speciﬁc and easy-of-use quantification methods is essential to study the population dynamics and, in this work, a new method for the simultaneous quantification of M. fructicola and M. laxa based on ddPCR technique was established. Under the optimized reaction conditions, consisting of 250 nM/500 nM of primers/probe sets concentration, 58°C as annealing temperature and 50 PCR cycles, the duplex-ddPCR assay was 200-fold sensitivive than duplex-Real Time qPCR assay, quantifying less than 1 copy μL-1 of target DNA in the PCR mixture. The results obtained with the validation assay performed on apricot and peach fruits, artificially inoculated with conidial suspensions containing different ratios of M. fructicola and M. laxa, showed a high correlation (R2=0.98) between the relative quantity of DNA of the two species quantified by ddPCR and qPCR, and a more accurate quantification by ddPCR compared to qPCR at higher concentrations of M. fructicola. The herein described method represents a useful tool for early detection of Monilinia spp. on stone fruits and for improving knowledge on the epidemiology of brow rot and interactions between the two prevalent Monilinia species.